MSME Financial Recording Training in The Karisma Creativa Group of Kadubeureum Village - Intan Puspanita; Winda Nurtiana; Septariawulan Kusumasari; Rifqi Ahmad Riyanto (MOVE: Journal of Community Service and Engagement, 2023)
This community service initiative aims to introduce the concept of basic financial recording and assist MSME business owners in recording their business activity transactions. The service activity is carried out in several stages, starting with identifying priority problems that need to be resolved. The next stage is to conduct socialization and training to help MSMEs in Kadubeureum Village with their financial recording. Through this activity, it was discovered that many MSME players do not separate their personal money from their business activities, making it difficult to determine their operational costs. With this activity, micro business owners in Kadubeureum Village can better understand the importance of financial recording for their business and are encouraged to record every business transaction on a daily basis.